Analisis Prinsip-prinsip Good Corporate Governance pada Perusahaan Pembiayaan - Antonius Kaban; Marlon Sihombing; Usman Tarigan (Universitas Medan Area, 2017)
The principles of Good Corporate Governance are important so that performance is increasing and beneficial to the stakeholders. The formulation of the problem of how Good Corporate Governance principles, obstacles, and actions to improve the principles of Good Corporate Governance in Â PT. XYZ Finance Region of North Sumatra. Combined research (Mixed Methods Research) Respondent only leaders with supervisor level until general manager Questionnaire data collection, observation and interview of respondent Descriptive statistic analysis, triangulation technique credibility test and transferability. PT. XYZ Finance of North Sumatera region runs the principles of Good Corporate Governance with: The principle of openness: 3.7 good. Accountability: 4.1 good. Accountability 3.1 is not good. Independence: 2.6 less good. Fairness: 3.2 is not good. Total value: 4,026 on either area. Two factors that play the role of internal factors, as a driver of success and external factors, which affect the successful implementation of Good Corporate Governance. Beyond these two factors, the most strategic aspect of supporting the implementation of Good Corporate Governance effectively depends on the quality, skill, credibility, and integrity of the various parties that drive the company's organs. Performance improvement plan in order to realize the principles of Good Corporate Governance in order to deliver the results as expected must meet the criteria of practical, time oriented, specific and committed.